Diversity, Equity, and Inclusion in Tenure & Promotion Workgroup Report and Recommendation - Salisbury University Faculty Senate (My University, 2021)
Diversity, Equity, and Inclusion (DEI) in Tenure & Promotion (TP) Workgroup's report and recommendations to the Faculty Senate, created September 16, 2021.
Keywords: Governance Consortium; Shared Governance